Enhanced Facilitation of Spatial Attention in Schizophrenia - Spencer, Kevin M. (2011)
OBJECTIVE: While attentional functions are usually found to be impaired in schizophrenia, a review of the literature on the orienting of spatial attention in schizophrenia suggested that voluntary attentional orienting in response to a valid cue might be paradoxically enhanced. We tested this hypothesis with orienting tasks involving the cued detection of a laterally-presented target stimulus. METHOD: Subjects were chronic schizophrenia patients (SZ) and matched healthy control subjects (HC). In Experiment 1 (15 SZ, 16 HC), cues were endogenous (arrows) and could be valid (100% predictive) or neutral with respect to the subsequent target position. In Experiment 2 (16 SZ, 16 HC), subjects performed a standard orienting task with unpredictive exogenous cues (brightening of the target boxes). RESULTS: In Experiment 1, SZ showed a larger attentional facilitation effect on reaction time than HC. In Experiment 2, no clear sign of enhanced attentional facilitation was found in SZ. CONCLUSIONS: The voluntary, facilitatory shifting of spatial attention may be relatively enhanced in individuals with schizophrenia in comparison to healthy individuals. This effect bears resemblance to other relative enhancements of information processing in schizophrenia such as saccade speed and semantic priming.